Fluxo gênico e diversidade genética em uma população manejada de mogno (swietenia macrophylla king, meliaceae) na Amazônia oriental - André, Thiago José de Carvalho (Instituto Nacional de Pesquisas da Amazônia - INPA, 2005)
Mahogany, Swietenia macrophylla, is the most valuable commercial forest species from the Neotropics and has been over-exploited along its range distribution. The present study investigated the patterns of pollen flow, genetic structure and the effects of selective logging on the genetic diversity of one managed mahogany population in Eastern Amazonia. Eight hipervariable microsatellite loci were used to estimate the genetic parameters using an automated DNA sequencer. The extension of pollen flow between trees in the population was estimated by parentage analysis of seedlings. The spatial and temporal genetic structure of the population was determined correlating the parentage level with the spatial distances and distances between the starting day of flowering between pair of trees. The number of alleles per locus (A), mean expected heterozygosity (He) mean observed heterozygosity (Ho), the number of unique multilocus genotypes (Go) and the inbreeding coefficient (f) were estimated for one post logging generation (seedlings) and the pre logging generation (adults) aiming to quantify the effects of the selective logging on the population genetic variability. Parentage analysis showed parents involved in the outcrossing of 19 out of 51 genotyped seedlings. The pollen flow between trees varied from 0.25 to 2.7 km (mean 1.5 km), a distance greater than expected if considering pollination by small insects. The data suggest rare inbreeding in the population probably due to the lack of spatial genetic structure and low flowering synchrony between related individuals. There was a significant reduction in the number of alleles, observed heterozygosity and unique multilocus genotypes in the post compared to the pre logging generation. The loss of genetic diversity probably occurred owing to the reduction of effective population size, which leads to the loss of alleles and limit possibilities to outcrossing, causing an excess of homozygous in the seedlings compared to the adults. The data presented here confirm the occurrence of genetic erosion in a logged population of mahogany and raised questions related to the conservation genetics of managed populations of tropical forest species.
Keywords: Fluxo gênico; Diversidade genética; Mogno